Controlled and highly effective ring‐opening polymerization of α‐chloro‐ε‐caprolactone using Zn‐ and Al‐based catalysts. Issue 9 (22nd February 2020) - Bolley, Anaëlle; Mameri, Samir; Dagorne, Samuel
Abstract: The present study details the highly effective and controlled ring‐opening polymerization (ROP) of α‐chloro‐ε‐caprolactone (1, αClεCL), a cyclic ester that has been little explored thus far in ROP catalysis, using Zn‐ and Al‐based catalysts [Zn(C6 F5 )2 (toluene)] (4 ), [ N, N ′‐bis(3, 5‐di‐ tert ‐butylsalicylidene)1, 3‐diaminopropanato]aluminium(III)benzyloxide (5 ) and [ N, N ′‐bis(3, 5‐di‐ tert ‐butylsalicylidene)1, 3‐diamino‐2, 2′‐dimethylpropanato]aluminium(III)benzyloxide] (6 ). Chain‐length‐controlled PαClεCL material is produced under solution ROP conditions, as deduced from GPC, NMR, MALDI‐TOF, and kinetic data. In contrast, the ROP of 1 is ill‐defined under bulk ROP conditions due to partial thermal degradation of the polymer chain (presumably through C–Cl cleavage), reflecting the limited stability of PαClεCL. The Al Catalysts 5 and 6 are highly active ROP catalysts of αClεCL at room temperature (TOF up to 2, 400 hr −1 ) to afford well‐defined P(αClεCL). In the case of Catalyst 6, carrying out the ROP of αClεCL under immortal conditions (with BnOH as chain transfer agent) is clearly beneficial to ROP activity and control, with no apparent side‐reaction of chloro‐functionalized PCL chains as the ROP proceeds. The controlled character of these ROPs was further exploited for the production of chain‐length‐controlled PLLA‐ b ‐PαClεCL diblocks through sequential ROP of l ‐lactide and αClεCL, affording copolymers with improved thermal and biodegradable properties. Abstract : The highly effective and controlled ring‐opening polymerization (ROP) of α‐chloro‐ε‐caprolactone (αClεCL) using Zn‐ and Al‐based catalysts is reported, and chain‐length‐controlled PαClεCL materials are obtained with narrow dispersity. The sequential ROP of l ‐lactide (LLA) and αClεCL allows the preparation of well‐defined PLLA‐ b ‐PαClεCL diblock copolymers.